NLRP3 inflammasome as a sensor of micro- and nanoplastics immunotoxicity - Alijagic, Andi; Hedbrant, Alexander; Persson, Alexander; Larsson, Maria; Engwall, Magnus; Särndahl, Eva (Frontiers in Immunology, 2023)
Micro- and nanoplastics (MNPs) are emerging pollutants with scarcely investigated effects on human innate immunity. If they follow a similar course of action as other, more thoroughly investigated particulates, MNPs may penetrate epithelial barriers, potentially triggering a cascade of signaling events leading to cell damage and inflammation. Inflammasomes are intracellular multiprotein complexes and stimulus-induced sensors critical for mounting inflammatory responses upon recognition of pathogen- or damage-associated molecular patterns. Among these, the NLRP3 inflammasome is the most studied in terms of activation via particulates. However, studies delineating the ability of MNPs to affect NLRP3 inflammasome activation are still rare. In this review, we address the issue of MNPs source and fate, highlight the main concepts of inflammasome activation via particulates, and explore recent advances in using inflammasome activation for assessment of MNP immunotoxicity. We also discuss the impact of co-exposure and MNP complex chemistry in potential inflammasome activation. Development of robust biological sensors is crucial in order to maximize global efforts to effectively address and mitigate risks that MNPs pose for human health.